VD_FINDINFO Jug / 2023 / 108 vom 7. April 2022 - VD Tribunal cantonal (2022)
ASSASSINAT, TENTATIVEDROIT PÉNAL, EXPULSIONDROIT PÉNAL, REJET DE LA DEMANDE | 180 al. 1 CP, 22 ad 112 CP, 66a al. 1 let. a CP, 19a ch. 1 LStup